APPLICATION OF WATERLOO MAPLE 9.5 AND WOLFRAM MATHEMATICA 5.1 SOFTWARE FOR ANALYTIC SOLVING OF CERTAIN NONLINEAR PARTIAL DIFFERENTIAL EQUATIONS OF PHYSICS - Stępień, Łukasz T. (Computer Science, 2013)
In the current paper some applications of the packet MAPLE (v. 9.5) for analytic solving ofcertain nonline partial differential equations have been presented. Additionally, for graphicpresentation of the found solutions packet MATHEMATICA (v. 5.1) has been applied.